Neoplastic Cerebral Aneurysm From Metastatic Nonsmall Cell Lung Carcinoma: Case Report and Literature Review. Issue 6 (23rd December 2017) - Omofoye, Oluwaseun A; Barnett, Randaline; Lau, Winnie; Trembath, Dimitri; Jordan, J Dedrick; Sasaki-Adams, Deanna M
Abstract: BACKGROUND AND IMPORTANCE: Intracranial cerebral aneurysms secondary to neoplastic etiology are a very rare occurrence. There have only been 5 published reports of intracranial cerebral aneurysms secondary to metastatic lung cancer. Four of those five previously published reports have been secondary to nonsmall cell lung carcinoma, and only 1 case caused subarachnoid hemorrhage. To our knowledge, this is the first report of a lung cancer-associated superior cerebellar artery aneurysm. CLINICAL PRESENTATION: A 41-yr old male presented with right-sided cerebellar hemorrhage. Cerebral angiogram was negative, but he was noted to have an underlying nonsmall cell carcinoma. His workup revealed a left upper lobe mass consistent with a diagnosis of metastatic lung carcinoma. A few weeks later, the patient represented with subarachnoid hemorrhage from a left superior cerebellar artery aneurysm that was new in comparison with a magnetic resonance angiography 19 d earlier. The aneurysm was remote to the surgical site, and the patient had a negative infectious workup, making an iatrogenic pseudoaneurysm or mycotic aneurysm unlikely. In the setting of metastatic cancer, a neoplastic cerebral aneurysm was the presumptive diagnosis. CONCLUSION: Intracranial neoplastic cerebral aneurysms are extremely rare entities, and a rare cause of subarachnoid hemorrhage. This diagnosis should be considered in patients who present with concurrent metastatic cancer and cerebral aneurysm or aneurysmal subarachnoid hemorrhage. Early initiation of chemotherapy may be beneficial in reducing the risk of tumor-particle embolization, but more research needs to be conducted to better understand this rare phenomenon.